The use of technology in civil and family oral trials as an innovative source of human rights in Mexico - Dra. Blanca Torres Espinosa; Carlos Ernesto Arcudia Hernández; Sara Berenice Orta Flores (Análisis Jurídico - Político)
The Declaration of the Rights of Man and of the Citizen of 1789 recognizes basic rights, including the right to life, liberty, security, equality, property and the expression of ideas and opinions through the press or any other medium. This would mark the starting point of freedom of expression, which today is complemented by the use of technology and the Internet. Since this historical event, people’s rights have evolved, and new rights have arisen in accordance with the times, such as the right to express oneself and to be communicated through the Internet, using appropriate devices. In 2013, the Mexican Constitution was reformed to recognize the right of people to be communicated, including access to the internet, in Articles 6 and 7. According to the United Nations Resolution of July 2, 2018 on the promotion and protection of all human rights—civil, political, cultural, economic and social rights, including the right to development—, the human right to have access to the internet is mentioned; however, Mexico had already included it in its regulatory framework since 2011. The final section of this paper focuses on the study of the use of technology and the Internet in the current regulations, as well as on the challenges faced by civil and family procedural law with the entry into force of the new Code of 2023.